Assessing the corrosion protection of 8-hydroxyquinoline-cerium (III) complex for carbon steel in a NaCl solution - Nguyen, Anh Son; Nguyen, Thuy Duong; Thi Xuan Hang, To; Vuong, Thi Vy Anh; Pham, Thu Thuy; Thai, Thu Thuy; Trinh, Anh Truc; Pébère, Nadine (Vietnam Journal of Science and Technology, 2024)
In the present study, a complex between 8-hydroxyquinoline and cerium (III) (Ce-HQ) was synthesized in the presence of triethylamine. Afterwards, the complex was characterized by Field Emission Scanning Electron Microscopy (FESEM), Fourier-transform infrared spectroscopy (FTIR) and Thermo-Gravimetric Analysis (TGA). The inhibition efficiency of the Ce-HQ complex for the corrosion of carbon steel, evaluated by both Electrochemical Impedance Spectroscopy (EIS) and Potentiodynamic Polarization (PP) plots, reached 90 % after 2 h of immersion in a 0.01 M NaCl solution. Then, EIS measurements were carried out to evaluate the effect of the Ce-HQ complex, as inhibitive pigment, after incorporation in a waterborne epoxy coating applied over carbon steel plate. The total resistance (Rtotal) of the coated sample containing the Ce-HQ complex was higher (3.6 x 107 Ω cm2), after 35 days of exposure in a 0.5 M NaCl solution than the values obtained for the coating without Ce-HQ. The results showed that the EP/Ce-HQ coating provided not only corrosion protection by the Ce (III) ions and 8HQ release at the metal/coating interface, but also improved the barrier properties. This work proposed a new type of inhibitive pigments which can be used to develop effective coatings for corrosion protection.